Influences of background factors on consumers’ purchase intention in China’s organic food market: Assessing moderating role of word-of-mouth (WOM) - Shimiao Li (Taylor & Francis Group, 2021)
The present study aims to clarify how background factors influence consumers’ intention of purchasing organic food from individual, social, and information perspectives (i.e., health consciousness, self-perceived vegetarian, as well as labeling). Another aim is to explore the moderating role of word-of-mouth (WOM) in relationship between purchase intention and purchase decision to fill in the intention-behavior gap in the field of behavior of purchasing organic food. The data were acquired through purposive sampling method by distributing questionnaires among organic food consumers. 280 out of 306 questionnaires were valid to proceed to statistical analysis. All proposed hypotheses were verified through structural equation modeling (SEM) and SPSS PROCESS regression analysis. As suggested from the study results, except for hedonistic motivation factor, the other background factors (i.e., individual, social, and information) significantly impacted consumers’ purchase intention. Moreover, the relationship between purchase intention and purchase decision was significantly moderated by word-of-mouth (WOM). The present study sheds light on how to motivate consumers’ purchase intention by stressing vital background factors from individual (i.e., purchase attitude and health consciousness), social (i.e., self-perceived vegetarian and environmental concern), and information perspectives (i.e., labeling and social media information). Besides, a novel insight is presented for marketers on how to deepen the relationship between consumers’ purchase intention and purchase decision via the moderating effect of word-of-mouth (WOM).